Physicochemical characteristics, fatty acids profile, health lipid indices and consumer acceptability of processed cheese prepared from camel milk blended with avocado powder - F. M. Ali , Rehab (jurnal1, 2024)
The aim of the current investigation was to evaluate the impact of different quantities of avocado fruit pulp powder (AFPP) (0, 5, 10, 15, and 20%) on the sensory properties, physicochemical properties, and fatty acid profile of Camel's milk processed cheese (CMPC). CMPC cheese represents the control sample without AFPP addition. At ratios of 100:0, 95:5, 90:10, 85:15, and 80:20, AFPP was used to substitute CMPC cheese (%, w/w). Standard official methods were used to analyze the proximate composition, mineral content, fatty acid profile, health lipid indices, as well as consumer acceptability of CMPC, AFPP, and binary mixtures of them. AFPP was rich in fat, protein, ash, and fibers (58.18, 8.19, 7.48, and 7.00%, respectively). CMPC is mainly composed of moisture (63.03 %), with 23.9%, % of crude protein, 9.15 % of lipids and3.92 % ash. Fat, fiber, ash and energy contents of fortified cheese samples increased significantly with the addition of AFPP. No significant differences were recorded in protein between control cheese samples and those cheese samples containing AFPP. The results also revealed that the K, Mg, Fe, and Zn content in CMPC cheese samples enriched with 20% AFPP were about 2.41, 1.18, 1.72, and 1.30-fold higher, respectively, when compared to control cheese without any addition of AFPP. In fortified cheese samples, the amounts of oleic, linoleic, and linolenic acids significantly increased as the AFPP dosage increased; however, the amounts of myristic, palmitic, and stearic acids decreased as the AFPP concentration increased. The reduction in atherogenic and thrombogenic indices of CMPC cheese samples with different concentrations of AFPP demonstrate the nutritional advantages of CMPC cheese enriched with avocado powder. The sensory evaluation results indicated that all processed cheese samples in the current investigation were acceptable and received high overall acceptability scores ranged from76.19 to 84.60